Magnetic nanoparticles draw solution for forward osmosis: Current status and future challenges in wastewater treatment - MhdAmmar Hafiz (14151687) (2022)
Forward osmosis is considered as the least energy intensive membrane process since it operates based on the osmotic pressure gradient. However, it is still considered as immature technology mainly due to the elevated cost for draw solution regeneration. Nevertheless, magnetic nanoparticles could be considered as a sustainable draw solute for forward osmosis due to high osmotic pressure and easy regeneration using magnetic force, but a significant development is still needed before implementing it for wastewater treatment and desalination. Herein, we analyzed the performance of the available magnetic nanoparticles draw solute and identified the challenges facing the use of magnetic nanoparticles as draw solute in the forward osmosis process. We first highlight the common synthesis methods of magnetic nanoparticles, and basics for generation of osmotic pressure using magnetic nanoparticles. Then, we analyzed the performance and limitations of available magnetic nanoparticles that were used as draw solute in the forward osmosis process. Later, we assessed the toxicity level of the magnetic nanoparticles and explored the regulations of using magnetic nanoparticles in the water treatment industry. Finally, new avenues of research were proposed to make magnetic nanoparticles draw solution more effective when applying it in desalination and wastewater treatment process. Other Information Published in: Journal of Environmental Chemical Engineering License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.jece.2022.108955